Income Mobility - Markus Jäntti; Stephen P. Jenkins (Institute for the Study of Labor (IZA), 2013)
This paper is prepared as a chapter for the Handbook of Income Distribution, Volume 2 (edited by A. B. Atkinson and F. Bourguignon, Elsevier-North Holland, forthcoming). Like the other chapters in the volume (and its predecessor), the aim is to provide comprehensive review of a particular area of research. We survey the literature on income mobility, aiming to provide an integrated discussion of mobility within- and between-generations. We review mobility concepts, descriptive devices, measurement methods, data sources, and recent empirical evidence.
Keywords: D31; I30; 330; intragenerational mobility; intergenerational mobility; income mobility; earnings mobility